Movement pattern training compared with standard strengthening and flexibility among patients with hip-related groin pain: results of a pilot multicentre randomised clinical trial. Issue 1 (23rd March 2020) - Harris-Hayes, Marcie; Steger-May, Karen; Bove, Allyn M; Foster, Stefanie N; Mueller, Michael J; Clohisy, John C; Fitzgerald, G Kelley
Abstract : Study design: Pilot, multicentre randomised clinical trial (RCT). Objectives: Assess viability of performing a definitive RCT and compare preliminary effects of movement pattern training (MoveTrain) and strengthening/flexibility (Standard) to improve function in people with chronic hip-related groin pain (HRGP). Background: To determine the best physical therapist-led intervention for patients with HRGP, we must understand treatment effects of different treatment modes. Methods: Forty-six patients (17M:29F; 29±5.3 years; body mass index 25.6±6.3 kg/m 2 ) with HRGP were randomised. MoveTrain included task-specific training to optimise biomechanics during daily tasks. Standard included strengthening/flexibility. Treatment included 10 visits/12 weeks and home exercise programme (HEP). Primary outcomes for feasibility were recruitment, retention, treatment adherence and treatment fidelity. Secondary outcomes were patient-reported function (Hip disability and Osteoarthritis Outcome Score (HOOS)), lower extremity kinematics and hip muscle strength. Results: We achieved target recruitment, and retention was excellent (91%). Patient session attendance was high (93%); however, reported HEP adherence (62%) was lower than expected. Physical therapists' adherence to treatment protocols was high (90%). Patients demonstrated high treatment receipt; 91% of exercises performed were rated independent. Both groups demonstrated clinically important improvements in function (HOOS) and muscle strength; however, there were no between-group differences (HOOS subscales, p≥0.13, strength, p≥0.34). Compared with Standard, MoveTrain demonstrated greater reductions in hip adduction (p=0.016) and pelvic drop (p=0.026) during a single leg squat. No adverse events were noted. Conclusion: Our experience in completing this RCT confirmed that a larger, multicentre RCT is feasible and highlighted modifications we will implement to optimise the future RCT. Trial registration number: NCT02913222 .